2014
DOI: 10.1021/nn5009319
|View full text |Cite
|
Sign up to set email alerts
|

Fast Response, Vertically Oriented Graphene Nanosheet Electric Double Layer Capacitors Synthesized from C2H2

Abstract: The growth and electrical characteristics of vertically oriented graphene nanosheets grown by radio frequency plasma-enhanced chemical vapor deposition from C2H2 feedstock on nickel substrates and used as electrodes in symmetric electric double layer capacitors (EDLC) are presented. The nanosheets exhibited 2.7 times faster growth rate and much greater specific capacitance for a given growth time than CH4 synthesized films. Raman spectra showed that the intensity ratio of the D band to G band versus temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
131
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 39 publications
3
131
1
3
Order By: Relevance
“…At 120 Hz, these two numbers are 0.6 mF cm À2 and 0.6 F cm À3 for our EOG/GCF electrodes. The corresponding phase angle at 120 Hz is À83 , comparable with the state of the art such as VOG on Ni substrate (À82 to À85 ) [8,11,12], POG in Ni foam (À82 ) [13], electrochemically reduced graphene oxide (ErGO) on Au (À84 ) [8], and patterned graphene CNT on metal coated silicon (À81.5 ) [23], but with a much larger volumetric capacitance when the whole electrode volume is considered. The frequency-dependent capacitance can also be estimated based on the method of Taberna et al [4] to define complex capacitance C c ðuÞ as C c ðuÞ ¼ C 0 ðuÞ À jC 00 ðuÞ ¼ 1=ðjuZÞ (2) where C 0 ðuÞ is the accessible capacitance at the corresponding frequency, while C 00 ðuÞ corresponds to energy dissipation due to irreversible process (resistive loss).…”
Section: Electrochemical Study and Frequency Responsementioning
confidence: 58%
See 1 more Smart Citation
“…At 120 Hz, these two numbers are 0.6 mF cm À2 and 0.6 F cm À3 for our EOG/GCF electrodes. The corresponding phase angle at 120 Hz is À83 , comparable with the state of the art such as VOG on Ni substrate (À82 to À85 ) [8,11,12], POG in Ni foam (À82 ) [13], electrochemically reduced graphene oxide (ErGO) on Au (À84 ) [8], and patterned graphene CNT on metal coated silicon (À81.5 ) [23], but with a much larger volumetric capacitance when the whole electrode volume is considered. The frequency-dependent capacitance can also be estimated based on the method of Taberna et al [4] to define complex capacitance C c ðuÞ as C c ðuÞ ¼ C 0 ðuÞ À jC 00 ðuÞ ¼ 1=ðjuZÞ (2) where C 0 ðuÞ is the accessible capacitance at the corresponding frequency, while C 00 ðuÞ corresponds to energy dissipation due to irreversible process (resistive loss).…”
Section: Electrochemical Study and Frequency Responsementioning
confidence: 58%
“…A comparison of the EOG/CCP electrode with others in the literature is helpful to reveal their performance difference. In the work by Miller et al [8], 0.6 mm thick VOG was grown on 75 mm thick Ni substrate to obtain a capacitance of 0.175 mF cm 2 at 120 Hz, which were further improved by Cai et al [12] to 0.53 mF cm 2 by using 2 mm thick VOG film on Ni substrate. Liu et al [9] reported electrodes of 20 mm thick ErGO foam deposited on Au substrate with a 120 Hz capacitance of 0.566 mF cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the VAGNA electrodes grown at the reduced temperature facilitated the access of electrolyte ions and thus showed better frequency response, which was favorable for their high-efficiency filtering applications. [85] Nitrogen doping in graphene has been shown to be able to induce n-type conductivity and enhance its electron transfer capability. By an in situ NH 3 plasma treatment, N-doped VAGNAs were obtained on flexible carbon cloth substrates, and N atoms were predominantly bonded to carbon in pyridinic structure (Figure 6a).…”
Section: Electric Double-layer Capacitors (Edlcs)mentioning
confidence: 99%
“…Ascribing to the abundant open pores formed by surrounding vertical graphene nanosheets, VAGNA/Ni electrodes enabled much improved electrochemical reaction kinetics and demonstrated as a near-ideal structure for EDLC electrodes being capable to operate at high frequencies, as shown in Figure 6e. [27,85] The design of VAGNAs minimized the electronic and ionic resistances and delivered a resistorcapacitor time constant less than 200 microseconds (about 1/5 of that of conventional EDLCs).…”
Section: Electric Double-layer Capacitors (Edlcs)mentioning
confidence: 99%
“…5 Generally the Raman D band to G band intensity ratio decreases with growth time indicating that crystalline order of the VOGN increases with nanosheet height, which increases approximately linearly with time at growth rates of 70 nm/minute using CH 4 and 190 nm/minute using C 2 H 2 . 6 Electrode capacitance at 120 Hz typically is in the 200 to 300 μF/cm 2 range, depending on VOGN growth conditions and growth time. The frequency response reported for EDLCs made using other external-surface-area nanomaterials is generally below that demonstrated by VOGN grown on nickel because of higher series resistance and/or distributed charge storage behavior.…”
mentioning
confidence: 99%